Comprehensive Analysis of AR Alterations in Circulating Tumor DNA from Patients with Advanced Prostate Cancer. (11th November 2019) - Ledet, Elisa M.; Lilly, Michael B.; Sonpavde, Guru; Lin, Edwin; Nussenzveig, Roberto H.; Barata, Pedro C.; Yandell, Mark; Nagy, Rebecca J.; Kiedrowski, Lesli; Agarwal, Neeraj; Sartor, Oliver
Abstract: Background: Somatic alterations in circulating tumor DNA (ctDNA) may be associated with treatment response or prognosis in prostate cancer (PCa). The goal was to characterize androgen receptor gene ( AR ) amplifications and mutations detected in ctDNA from patients with PCa and to further understand the somatic genetic heterogeneity of advanced prostate cancer. Patients and Methods: This study included a heterogeneous group of 892 patients with advanced PCa (predominantly castrate‐resistant prostate cancer) with AR alterations detected in ctDNA that underwent next‐generation sequencing of 54 to 73 genes via Guardant360 testing (Guardant Health, Inc., Redwood City, CA). Distribution and summary of AR alterations detected, the association of AR alterations with other genes, and a pathway analysis are reported. Results: The median absolute plasma copy number of AR amplifications was 3.3 (range, 1.2–165.2). Many patients had multiple AR mutations; a total of 112 unique mutations were identified in AR, including L702H (25%), T878A (14%), H875Y (11%), W742C (8%), W742L (4%), F877L (2%), and T878S (2%). Other ctDNA gene alterations in the Guardant assays included TP53 (50%), MYC (34%), BRAF (32%), PIK3CA (29%), MET (25%), CDK6 (26%), EGFR (24%), FGFR1 (21%), and APC (12%). Many of these non‐ AR alterations are not tissue verified in other studies. AR amplification cosegregated with alterations in MYC ( p < .001), BRAF ( p < .001), PIK3CA ( p < .001), MET ( p < .001), CDK6 ( p < .001), EGFR ( p < .001), FGFR1 ( p = .391), and more. Alterations in APC were significantly associated with mutations in AR ( p < .001). Conclusion: Several AR alterations and concomitant non‐ AR alterations that associate with drug resistance were detected. These findings provide additional insights into the heterogeneity of advanced prostate cancer. Implications for Practice: The goal was to characterize androgen receptor gene ( AR ) amplifications and mutations detected in circulating tumor DNA (ctDNA) from patients with prostate cancer in relation to non‐ AR gene alterations detected in the ctDNA landscape. The study included 892 patients with prostate cancer with AR alterations in ctDNA. AR alterations were significantly associated with other gene alterations detected in ctDNA. The common AR mutations found are linked to resistance to abiraterone, enzalutamide, or bicalutamide. Characterization of the circulating AR landscape and gene alterations provides potential additional insight into the somatic genetic heterogeneity of advanced prostate cancer. Abstract : This article characterizes AR amplifications and mutations detected in circulating tumor DNA from patients with prostate cancer, providing insight into the heterogeneity of advanced prostate cancer.